Crescimento inicial do cafeeiro irrigado com água salina e salinização do solo - Figueirêdo, Vladimir B. [UNESP] (2006)
The coffee crop is expanding to new areas with not enough studies about its response to saline irrigation water. The initial growth of coffee plant was evaluated, in greenhouse at the Engineering Department of the Federal University of Lavras (UFLA), under different levels of irrigation water salinity. The completely randomized design was used with 6 treatments (S0 = 0.0 dS m -1, S1 = 0.6 dS m -1, S2 = 1.2 dS m -1, S3 = 1.8 dS m -1, S4 = 2.4 dS m -1 and S5 = 3.0 dS m -1) and 4 replications. The irrigation was accomplished according to soil water retention curve and resistance block reading, restoring the soil water content to its field capacity. It was verified that water salinity affected the plants characteristics significantly. The water salinity above 1.2 dS m -1 caused damage to plant development resulting, in some cases, in death of plants. The leaf area of plant was the variable most affected by salinity of irrigation water. By the end of the experiment, the soil was classified as saline-sodic.